2012
DOI: 10.1088/0031-9120/48/1/35
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the photoelectric effect inductively

Abstract: Research has shown that students have difficulty understanding the underlying process of the photoelectric effect. Thus, this study sought to utilize an inductively situated lesson for teaching the photoelectric effect, hypothesizing that this type of enquiry would help learners delve deeper into the principles of the phenomenon and provide a better background for its quantification. The lesson was conducted with a group of fifteen high-school physics students and a computerized simulated experiment was utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
0
16
0
2
Order By: Relevance
“…This phenomenon is in conflict with prior, classical reasoning. Several selected articles addressed the understanding of waveparticle duality [1,4,5,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Ireson and Ayene et al researched existing student views of undergraduate students using cluster analysis [20,24,25].…”
Section: A Wave-particle Dualitymentioning
confidence: 99%
“…This phenomenon is in conflict with prior, classical reasoning. Several selected articles addressed the understanding of waveparticle duality [1,4,5,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Ireson and Ayene et al researched existing student views of undergraduate students using cluster analysis [20,24,25].…”
Section: A Wave-particle Dualitymentioning
confidence: 99%
“…In general, the theorem does not hold in scalar-tensor gravity: one needs to impose that the effective stressenergy tensor T (φ) ab of the Brans-Dicke-like scalar field of the theory is time-independent in order for the metric to be static (this requirement is usually achieved by imposing that φ is time-independent, but is also obtained by a stealth field φ [29,30]). The failure of the theorem in the presence of time-dependent scalars opens the door for new phenomenology in scalar-tensor gravity which is unknown in General Relativity.…”
Section: The Jebsen-birkhoff Theorem In Scalar-tensor Gravitymentioning
confidence: 99%
“…Photoelectric effect is one of the important quantum physics topics that play a crucial role in understanding the photon model of light (McKagan et al, 2009;Wong et al, 2011). Unfortunately, the previous researches reported that most of the students from different educational levels have serious learning difficulties in understanding the basic aspects of photoelectric effect such as interpreting experimental set-up, predicting experimental results and its' relation to the photon model of light (De Leone & Oberem, 2004;McKagan et al, 2009;Sokolowski, 2013;Steinberg et al, 1996). Especially, the university level quantum physics courses cover such topics so rapidly that most of learners cannot grasp the fundamentals of the concept (Asikainen & Hirvonen, 2009).…”
Section: Introductionmentioning
confidence: 99%